Microwave irradiation technique for synthesis of zeolite A - Harun, Mohd. Razif; Shuhada, A. N.; Triwahyono, Sugeng; Abdul Jalil, Aishah (2007)
Synthesization of Zeolite A from colloidal silica was performed by means of microwave irradiation technique under different conditions and was compared with hydrothermal technique. The molar composition at 1 Al203: 1.96 SiO2: 3.165 Na2O: 128 H2O. X-Ray Diffraction (XRD) and Scanning Electron Microscope (SEM) were used to characterize zeolite A. XRD results for all samples demonstrated a typical diffraction peak of zeolite A. SEM images show almost no-different in crystal size of zeolite A synthesized by microwave irradiation and hydrothermal technique. Thus, we concluded that crystallization of zeolite A has occurred rapidly by microwave irradiation. Microwave technique is a time and energy saving due to crystallization time and higher heating rate as compared to hydrothermal technique.